Tracking the activities of a body of inquiry - Лук'янчиков, Євген Дмитрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
It is analyzed the character of the powers of agencies of inquiry in the field of criminal procedure activity and enforcement operations acts.